Этнокультурные особенности цветообозначений в крымскотатарском фольклоре (на материале пословиц и народных песен) - Гафарова, Р.И. (Культура народов Причерноморья, 2013)
Внимание к цвету присуще культуре каждого народа, поскольку он обладает
эмоциональным воздействием на читателя. В статье рассматриваются особенности семантики
колоративов в крымскотатарской паремиологии и народно-песенном искусстве. Проведенный лексико-
семантический анализ прилагательных цветообозначения обосновывает универсальность категории
цветовосприятия крымскотатарского фольклора и достаточно четко выявляет национально-
специфические особенности семантического пространства данного пласта лексики. Увага до кольору притаманне культурі кожного народу, оскільки він володіє емоційним
впливом на читача. У статті розглядаються особливості семантики колоратівов у
кримськотатарській пареміології і народно-пісенному мистецтві. Проведений лексико-семантичний
аналіз прикметників цветообозначенія обгрунтовує універсальність категорії кольоросприйняття
кримськотатарського фольклору і досить чітко виявляє національно-специфічні особливості
семантичного простору даного пласта лексики. Attention to the color characteristic of the culture of every nation, because it has an emotional impact
on the reader. The article discusses the features of the semantics of a Crimean Tatar kolorativov paremiology
and folk-song art. Conducted by the lexical-semantic analysis of adjectives tcvetooboznachenija proves the
universality of the category of color perception of the Crimean Tatar folklore and quite clearly reveals the
national specifics of the semantic space of the reservoir vocabulary.
Relevance of represented research is caused by keen interest of modern linguistics in research of language
conceptualization of the world and special attention in studying of lexicon of color designation as reprezentant
of national cultures. The kolorativ lexicon and its concrete semantic filling as a part of proverbs and national
songs of crimeantatar language remains low-investigated.
Functioning of color designation of crimeantatar language in paremiological lexicon and lexicon of national
and song lyrics opens a national and cultural originality of crimeantatar culture.
Research of kolorativ words in paremiological units reveals unconditional leadership in rate and existence in
structure of value additional this of white and black color and in some cases they lose direct, color sense.
Supervision showed that in national songs achromatic and chromatic colors coexist on an equal footing. In the
texts the most frequent are lexemes white, black, blue, red and yellow, that is marked colors traditionally
allocated by the person. They realize the esthetic opportunities at creation of the primary figurativeness based
on a direct denotative relatedness of words.